Moments Worth Holding: Reclaiming Psychological Well-Being Through Appreciation of Everyday Beauty - Angela Olivia Lubis; Zarina Akbar; Mira Ariyani (Department of Psychology, Faculty of Education, Universitas Negeri Surabaya, 2025)
In our fast-paced and distracted modern lives, simple moments of aesthetic significance are often overlooked, even though everyday beauty has significant potential to strengthen individuals' psychological well-being. This study aims to examine how appreciation of everyday beauty contributes to the restoration and strengthening of mental health. Using a literature review approach, 27 national and international scientific articles published from 2015-2025 were thematically analyzed from various databases such as Google Scholar, PubMed, ScienceDirect, EBSCO, and Scopus. The studies covered the themes of aesthetic experience, positive emotions, self-reflection, psychological resilience, and meaning-making in everyday contexts. The results show that appreciation of everyday beauty - whether in the form of nature, art, moral actions, specific achievements or accomplishments, or social relationships - contributes to increased positive affect, gratitude, meaning in life, and emotional flexibility. In addition, aesthetic experience-based interventions such as beauty journaling and narrative reflection were found to be effective in increasing happiness and reducing stress symptoms. These findings confirm that Appreciation of Beauty and Excellence (ABE) is a relevant character strength as a humanistic, low-cost, inclusive, and contextualized psychological recovery mechanism, and can be an important foundation for the development of promotive strategies in the mental health of Indonesians.